Impact of sprawl on the peri-urban areas - Onaiwu, Daniel Nosakhare; Onaiwu, Faith Osagioduwa (Penerbit Universiti Kebangsaan Malaysia, 2019)
Urban sprawl is a major challenge on the spatial growth of settlements in the 21st century. It is often confined to the peri-urban areas, and its impact on the social, economic, and environmental conditions of cities. The present study examined the impact of sprawl on the peri-urban areas of Benin City, Nigeria. It used a sample survey of 390 respondents that were selected in six suburban strata of road corridors radiating from the central business district (CBD) of Benin City. A sample size of 65 respondents was used in each stratum because of the sparse population. The instrument administered to the household heads was a likert-type. The data from the study were descriptively analysed, using frequencies and percentages. Analysis of variance was used to test the significance of the spatial variability of the impact between the strata. There was a significance difference between the six strata in the combined dependent variables. The results revealed indiscriminate dumping of solid waste, increased travel costs, high crime rate, increased cost of infrastructure, and land conversion as major impact on the peri-urban areas of Benin City. The impact of agricultural land conversion, solid waste and crime were significant. It was recommended that a master plan should be prepared for Benin City at a regional setting to segregate agricultural land from other urban land uses, the high crime in peri-urban areas should be checked by government and waste dumps should be properly sited.